Activated Growth Factors (AGF), an Advanced Platelet-Rich Plasma (PRP) Modality, as a Novel Biological Treatment for Partial Anterior Cruciate Ligament Tears: A Case Report - Hidayat, Rachmat; Kemas Abdul Mutholib Luthfi; Olivia Azalia Putri; Sony Sanjaya; Linda Purnama; Sonya Syarifah; Nadia Khoirina; Abu Bakar; Rashidah Unaib Al Zayid; Reisha Notonegoro (Sriwijaya Journal of Surgery, 2025)
Introduction: Partial anterior cruciate ligament (ACL) ruptures present a complex clinical challenge. Traditional treatment options, including conservative management and surgical reconstruction, often yield unpredictable outcomes and extended recovery periods. This case report explores the potential of activated growth factors (AGF), an advanced platelet-rich plasma (PRP) modality, as a novel biological treatment strategy for partial ACL tears. Case presentation: A 39-year-old male presented with right knee pain and instability following a twisting injury sustained during exercise. Magnetic resonance imaging (MRI) confirmed a partial tear of the anteromedial bundle of the ACL. The patient was treated with a series of three intra-articular injections of AGF, administered at weekly intervals. The AGF was prepared using a proprietary protocol aimed at optimizing growth factor concentration and release. The patient's progress was meticulously monitored through clinical evaluations and functional assessments at 3 and 6 months post-treatment. Conclusion: This case suggests that AGF may offer a promising alternative for the treatment of partial ACL tears, potentially facilitating accelerated healing and improved clinical outcomes. Further research, including controlled trials, is warranted to validate these findings and establish the efficacy and safety of AGF in a larger patient population.